Correlation of Maternal Obesity and Exclusive Breastfeeding - Reza Saeidi; Mahboobe Gholami (Mashhad University of Medical Sciences, 2019)
Background: Many factors affect exclusive breastfeeding, include method of delivery, parity, maternal age and education, smoking, ethnicity, pregnancy complications, infant health, and environmental factors such as hospital practices, and social support. Recently, maternal obesity has been suggested as a risk factor for poor breast-feeding practices whose role has not yet been completely determined. This study was conducted to evaluate the effect of maternal obesity on exclusive breastfeeding. Methods: This Cross sectional study was carried out among women receiving prenatal care by midwives at the health center of Neyshabur University of Medical Sciences during 2014-2016. Data regarding maternal and neonatal variables were gathered. To analyze the data, Chi-squared test was run to determine the association between categorical variables. Results: Planned feeding method, educational level, employment status, and gestational age were the four strongest predictors for poor breast-feeding practices at discharge. Method of delivery, gestational diabetes, and maternal hypertension and maternal obesity were significantly associated with exclusive breastfeeding at discharge (p